EFFECT OF PRESTRESSING FORCE ONTORSION RESISTANCE OF CONCRETE BEAMS - Husain M. Husain; Nazar K. Oukaili; Muyasser M. Jomaa'h (Journal of Engineering, 2007)
This study presents an experimental and theoretical investigation of torsion behavior of prestressed concrete rectangular beams without ordinary (or typical) reinforcement. Two concrete beams with concentric prestressing tendons (6-strands of 7 wires) and two plain concrete beams were tested in this investigation with f'c= 44MPa was used. Experimental results showed that the ultimate torsional strengths increased by about 70% for the tested beams containing concentric prestressed strands over the plain concrete beams. Also the angle of twist decreased (68.8%).Crack patterns and the effect of compressive force due to prestressing tendons and high strength concrete can be denoted from the helical mode of single crack at midspan of the beams under testing and from the sudden failure mode. In the analytical work P3DNFEA (Program, three-dimensional nonlinear finite element analysis), by Al-Shaarbaf has been utilized. Three dimensional nonlinear quadratic 20 -node brick elements were used to model the concrete, while, the prestressing strands were modeled by embedded representation. Reinforcing bars (Prestressing strands) were assumed to be capable of transmitting axial forces only. It was found that the general behavior of the finite element showed good agreement with observations and results from the experimental tests.